Impedance Spectroscopy Analysis of PbSe Nanostructures Deposited by Aerosol Assisted Chemical Vapor Deposition Approach - Sadia Iram (MDPI AG, 2021)
This research endeavor aimed to synthesize the lead (II) diphenyldiselenophosphinate complex and its use to obtain lead selenide nanostructured depositions and further the impedance spectroscopic analysis of these obtained PbSe nanostructures, to determine their roles in the electronics industry. The aerosol-assisted chemical vapor deposition technique was used to provide lead selenide deposition by decomposition of the complex at different temperatures using the glass substrates. The obtained films were revealed to be a pure cubic phase PbSe, as confirmed by X-ray diffraction analysis. SEM and TEM micrographs demonstrated three-dimensionally grown interlocked or aggregated nanocubes of the obtained PbSe. Characteristic dielectric measurements and the impedance spectroscopy analysis at room temperature were executed to evaluate PbSe properties over the frequency range of 100 Hz–5 MHz. The dielectric constant and dielectric loss gave similar trends, along with altering frequency, which was well explained by the Koops theory and Maxwell–Wagner theory. The effective short-range translational carrier hopping gave rise to an overdue remarkable increase in ac conductivity (σac) on the frequency increase. Fitting of a complex impedance plot was carried out with an equivalent circuit model (Rg Cg) (Rgb Qgb Cgb), which proved that grains, as well as grain boundaries, are responsible for the relaxation processes. The asymmetric depressed semicircle with the center lower to the impedance real axis provided a clear explanation of non-Debye dielectric behavior.